Necroptosis modulated by autophagy is a predominant form of melanoma cell death induced by sanguilutine - Hammerová, Jindřiška; Uldrijan, Stjepan; Táborská, Eva; Vaculová, Alena Hyršlová; Slaninová, Iva (Biological chemistry, 2012)
We show that the plant quaternary benzo[c]phenanthridine alkaloid sanguilutine (SL) is a strong inducer of caspase-independent non-apoptotic death in human melanoma cells. Necrostatin-1, a specific inhibitor of necroptosis, completely reversed the cytotoxic effect of SL, suggesting that necroptosis was a predominant type of cell death induced by SL in these cells. In addition, we showed that SL can trigger an autophagic response, as confirmed by GFP-LC3 puncta formation and LC3-II accumulation. Interestingly, we observed a significant decrease in the viability of melanoma cells treated with combination of autophagy inhibitors (3-methyladenine, bafilomycin-A1 and LY294002) and SL. Our results further indicated that autophagy may serve as a pro-survival mechanism, delaying the induction of necroptosis in melanoma cells. The ability of SL to induce caspase-independent non-apoptotic cell death (necroptosis) suggests its possible therapeutic potential in the treatment of apoptosis-resistant melanoma tumours. Furthermore, SL might serve as a useful tool for studying the mechanisms of necroptosis and autophagy induction and the interplay between these two processes.
Keywords: Imidazoles; Gene Expression Regulation, Neoplastic; Microtubule-Associated Proteins; autofagie; viabilita buněk; protinádorové látky; imidazoly; Cell Line, Tumor; Adenine; indoly; Benzophenanthridines; regulace genové exprese u nádorů; adenin; Cell Survival; proteiny asociované s mikrotubuly; benzofenantridiny; nekróza; Caspases; Melanoma; kaspasy; Autophagy; lidé; Necrosis; Humans; Indoles; protoonkogenní proteiny c-bcl-2; Proto-Oncogene Proteins c-bcl-2; nádorové buněčné linie; melanom; Antineoplastic Agents